The Effect of Workload, Incentives, and Work Motivation on Nurse’s Performance Mediated by Job Satisfaction - Afrah Afifah Salsabila; Oscar Jayanegara (Dinasti Publisher, 2025)
This research aimed to analyze the Effect of Workload, Incentives, and Work Motivation on Nurse Performance with Job Satisfaction as a mediating variable. The study employed a quantitative research approach and hypothesis testing. Data was collected using total sampling with a Likert scale (1-5) questionnaire from 165 respondents. The data was analyzed using the Partial Least Squares Structural Equation Model (PLS-SEM). The results indicate that Workload has a negative effect on job satisfaction. Incentives have a positive effect on job satisfaction. Work motivation has a positive effect on job satisfaction. Workload has a negative effect on nurse performance. Incentives have a positive effect on nurse performance. Work motivation has a positive effect on nurse performance. Job Satisfaction has a positive effect on nurse performance. Job satisfaction has a negative effect and mediates the effect of workload on the performance of nurses. Job satisfaction has a positive effect and mediates the effect of incentives on the performance of nurses. Job satisfaction has a positive effect and mediates the effect of work motivation on the performance of nurses.